Mentoring scheme design - Garvey, Bob (London : SAGE Publications: SAGE Business Cases Originals, 2021)
This case allows students to analyze the design and implementation of a new mentoring scheme at Manufacturing Co., a pseudonym based on a real-world international engineering business. The company is operating in a competitive environment, and recently developed an international change strategy to combat these competitive threats. A key philosophy of the strategy was the idea of "the common approach" for everything. In effect, this meant all the development programs around the world were to be designed, implemented, and evaluated by paying attention to the worldwide company objectives. Senior leaders believed that this "common approach" would deliver the desired results across all sections of the company and move the business as one in the same direction. At the center of the Organizational Change and Development program was a mentoring scheme.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mentoring in business -- Case studies; Employees -- Coaching of -- Case studies